Piezoelectric surgery in implant dentistry: clinical applications - Lydia Masako Ferreira; José Luis Gonçalves Bretos; Mônica Talarico Dualibi; Flávio de Ávila Kfouri; Silvio Eduardo Dualibi (Faculdade São Leopoldo Mandic, 2009)
Pizosurgery has therapeutic characteristics in osteotomies, such as extremely precise, selective and millimetric cuts and a clear operating field. Piezoelectricity uses ultrasonic frequencies, which cause the points specially designed for osteotomy to vibrate. The points of the instrument oscillate, allowing effective osteotomy with minimal or no injury to the adjacent soft tissues, membranes and nerve tissues. This article presents the various applications of piezoelectricity in oral implant surgery such as: removal of autogenous bone; bone window during elevation of the sinus membrane and removal of fractured implants. The cavitational effect caused by the vibration of the point and the spray of physiological solution, provided a field free of bleeding and easy to visualize. The study showed that the piezoelectric surgery is a new surgical procedurethat presents advantages for bone cutting in many situations in implant dentistry, with great advantages in comparison with conventional instrumentation. Operating time is longer when compared with that of conventional cutters.